The impact of financial literacy, financial technology, and financial inclusion on SME business performance in Malang Raya, Indonesia - Rahadjeng, Erna Retno; Pratikto, Heri; Mukhlis, Imam; Restuningdiah, Nurika; Mala, Iva Khoiril (Journal of Social Economics Research, 2023)
The purpose of this study is to determine the relationship between financial literacy, financial technology, and financial inclusion and the business performance of SMEs in Malang Raya, Indonesia. Looking at various cases related to financial progress, all of which are turning to technology to ensure time efficiency, there is a need for further development related to research on financial technology, and financial inclusion for SMEs’ business performance in Malang Raya. The analysis in this study used bibliometrics and PLS. Bibliometrics is used to find relationships that will later become new things. Before the bibliometric analysis, this research looked for references to research through Publish or Perish, so more than 200 reputable journals based on electronics were found in accordance with this study. Furthermore, filters related to the scope are more specifically related to financial technology and the inclusion of SMEs’ performance. So fintech is being discovered as a novelty between financial literacy and financial inclusion. The second analysis examines the influence of financial literacy, financial technology, and, financial inclusion on the business performance of SMEs. The results of this study using PLS show that financial literacy has a positive and significant effect on the business performance of SMEs. Financial technology does not affect SMEs’ business performance, and lastly, financial inclusion has a positive and significant effect on SMEs’ business performance. The limitation of this study is related to the object of research that still focuses on Malang Raya.